CORELATION OF PARENTS' PROFILES OF CHILDREN WITH LATE CLEFT REPAIR IN SURABAYA CLEFT LIP AND PALATE CENTRE (JANUARY 2015–DECEMBER 2017) - Ningrum, Laras Puspita; Saputro, Iswinarno Doso; Zarasade, Lobredia (Universitas Airlangga, 2020)
Highlights: Economic factors and insufficient information about cleft palate treatment was the primary cause of delayed repairs,except for Parents' education levels. The essential responsibility of primary care physicians is to provide education on treatment stages to minimize delays. Abstract: Introduction: Optimal time of Cleft palate repair is during the 10 to 12 month of age. In this time produce far natural results in terms of speech because it enabled the maturation of scar tissue postoperatively. The soft palate must function properly before the patient starts learning to talk, otherwise speech disorders such as persistent rhinolalia aperta might arise. In pediatric patients, the role of parents is very important on adherence to therapy. Methods: This is a cross-sectional study. The first study group was parents of patients who had surgical repair before two years old and the second group was the parents of patients who had repair after two years old. We compared age, monthly income, education level, number of children, and residential distance from Surabaya of the two groups. Results: The data of this study were obtained from the medical records of patients with cleft lip surgery at CLP Center Surabaya in 2015th-2017th with total of 358 patients, 172 were female and 186 were male. 52 patients with delayed cleft palate surgery. Patients' parents in both groups were mostly 31- 40 years old, were high school graduated, has one child, earned less than 1.5 million rupiah a month, and lived less than 100 kms from Surabaya. From the statistical results, parent's income has the strongest correlation with the patient's age in cleft palate surgery (-2.7). A negative coefficient means that the less parent's income, the more patient likely had delayed cleft palate surgery. While other factors found weak and very weak correlations. Conclusions:The results form patient's parents' interview, concluded that besides economic factors, the lack of information cleft palate treatment is the key factors that contributed to the delay of cleft palate repair. The education level does not affect the delay in cleft palate surgery, because even in high educated parents, sometimes they don't understand the stages of cleft lip and palate treatment. This study emphasized the necessity to educate about the stages of surgery by primary care physicians, to minimize delays.